Missionaries, converts, and rabbis the evangelical Alexander McCaul and Jewish-Christian debate in the nineteenth century - Ruderman, Daṿid 1944- (Philadelphia University of Pennsylvania Press, 2020)
"This book is about the English missionary Alexander McCaul, who wrote many works aiming to convert Jews to Christianity. The book is about people who are caught between belief practices: Philo-Semitism, Philo-Christianity, Anti-Semitism, and Anti-Christianity"--
Published in association with the Herbert D. Katz Center for Advanced Judaic Studies of the Univerrsity of Pennsylvania
Includes bibliographical references and index
Archivierung/Langzeitarchivierung gewährleistet
Keywords: McCaul, Alexander -- 1799-1863; London Society for Promoting Christianity amongst the Jews; Missions to Jews -- History -- 19th century; Judaism -- Relations -- Christianity -- History -- 19th century; Christianity and other religions -- Judaism -- History -- 19th century